Aspirin use and bleeding events during thrombocytopenia after autologous stem-cell transplantation for multiple myeloma - Neuendorff, Nina Rosa; Boshikova, Boryana; Frankenstein, Lutz; Kirchner, Marietta; Rohde, Christian; Goldschmidt, Hartmut; Frey, Norbert; Müller-Tidow, Carsten; Jordan, Karin; Sauer, Sandra; Janssen, Maike (Frontiers in oncology, 2023)
Background: In patients with cardiovascular (CV) comorbidities that necessitate antiplatelet therapy (APT), its optimal management during chemotherapy-induced thrombocytopenia remains elusive, as the risk of bleeding has to be balanced against the risk of CV events. The purpose of this study was to assess the risk for bleeding with APT during thrombocytopenia in patients with multiple myeloma undergoing high-dose chemotherapy and subsequent autologous stem-cell transplantation (ASCT) with and without acetylsalicylic acid (ASA) as comedication. Methods: We assessed patients who underwent ASCT at the Heidelberg University Hospital between 2011 and 2020 for bleeding events, management strategies for ASA intake during thrombocytopenia, transfusion requirements, and the occurrence of CV events. Results: There were 57/1,113 patients who continued ASA until at least 1 day after ASCT; thus, a continuous platelet inhibition during thrombocytopenia was assumed. Most of the patients (41/57) continued ASA until they had a platelet count of 20-50/nl. This range reflects the kinetics of thrombocytopenia and nondaily measurements of platelets during ASCT. A tendency toward a higher risk for bleeding events in the ASA group was demonstrated (1.9% (control group) vs. 5.3% (ASA), p = 0.082). The risk factors for bleeding in multivariate analysis were the duration of thrombocytopenia < 50/nl, a history of gastrointestinal bleeding, and diarrhea. The factors predicting the duration of thrombocytopenia were age >60 years, a hematopoietic stem-cell transplantation comorbidity index ≥3, and an impaired bone marrow reserve at admission. CV events occurred in three patients; none of them took ASA or had an indication for APT. Conclusions: The intake of ASA until thrombocytopenia with a platelet count of 20-50/nl appears safe, although an elevated risk cannot be excluded. If ASA is indicated for the secondary prevention of CV events, the evaluation of risk factors for bleeding and a prolonged time of thrombocytopenia before conditioning is crucial to adapt the strategy for ASA intake during thrombocytopenia.
Gesehen am 20.06.2023